Comparison of microleakage of MTA plugs prepared with normal saline and egg white - Abas Ali Khademi; Hossein Zarezadeh (Isfahan University of Medical Sciences, 2011)
Introduction: Different techniques are used to treat open apices, including MTA plugs. Regarding MTA's long setting time, which results in greater microleakage during the first hours after its placement and its difficult handling properties, the aim of this study was to evaluate microleakage of MTA plugs mixed with normal saline and egg white.Materials and Methods: Seventy extracted human single-rooted teeth were randomly divided into two groups of 30 and two positive and negative control groups of 5. In group 1, an MTA plug mixed with normal saline was placed in each canal. In group 2, albumin was mixed with MTA. In the positive control group, a #80 gutta-percha was placed inversely in each canal. In the negative control group, the canal was obturated with MTA and the access cavity was filled with sticky wax. Root surfaces, except for the apical 2 mm, were covered with 2 layers of nail varnish. All the teeth were placed in the bacterial leakage evaluation system and were sterilized with ethylene oxide gas. Then they were transferred to anti-serum vials containing BHI solution. A fresh solution of Enterococcus faecails was injected into the system every 3 days. The samples were evaluated daily for 90 days for turbidity was. Data was analyzed using Kaplan-Meier survival analysis (α = 0.05).Results: Turbidity rates in groups 1 and 2 were 76.7% and 60%, respectively, with average turbidity times of 27.06 and 42.13 days. No significant differences were noted between the two groups (p value = 0.151).Conclusion: There were no significant differences in microleakage between MTA plugs mixed with albumin and normal saline. The first combination can be used to improve the setting time and handling properties of MTA. Key words: Apexification, Microleakage, MTA plug, Normal saline.